Combinatorial Optimization Second International Symposium, ISCO 2012, Athens, Greece, April 19-21, 2012, Revised Selected Papers - Mahjoub, A. Ridha; Markakis, Vangelis; Milis, Ioannis; Paschos, Vangelis Th.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the thoroughly refereed post-conference proceedings of the Second International Symposium on Combinatorial Optimization, ISCO 2012, held in Athens, Greece, in April 2012. The 37 revised full papers presented together with 4 invited talks were carefully reviewed and selected from 94 regular and 30 short submissions. They present original research on all aspects of combinatorial optimization, ranging from mathematical foundations and theory of algorithms to computational studies and practical applications.
Structure Theorems for Optimum Hyperpaths in Directed Hypergraphs -- Branch-and-Price Guided -- The New Faces of Combinatorial Optimization -- Models and Algorithms for the Train Unit Assignment Problem -- The Minimum Stabbing Triangulation Problem: IP Models and Computational Evaluation -- Using Symmetry to Optimize over the Sherali-Adams Relaxation -- A Second-Order Cone Programming Approximation to Joint Chance-Constrained Linear Programs -- Semidefinite Relaxations for Mixed 0-1 Second-Order Cone Program -- The Non-Disjoint m-Ring-Star Problem : Polyhedral Results and SDH/SONET Network Design.-The Uncapacitated Asymmetric Traveling Salesman Problem with Multiple Stacks -- Polyhedral Analysis and Branch-and-Cut for the Structural Analysis Problem -- Extended Formulations, Nonnegative Factorizations, and Randomized Communication Protocols -- An Algebraic Approach to Symmetric Extended Formulations -- Dual Consistent Systems of Linear Inequalities and Cardinality Constrained Polytopes -- Minimum Ratio Cover of Matrix Columns by Extreme Rays of Its Induced Cone.-The Uncapacitated Asymmetric Traveling Salesman Problem with Multiple Stacks -- Polyhedral Analysis and Branch-and-Cut for the Structural Analysis Problem -- Extended Formulations, Nonnegative Factorizations, and Randomized Communication -- An Algebraic Approach to Symmetric Extended.-On the Hop Constrained Steiner Tree Problem with Multiple Root.-Structure Theorems for Optimum Hyperpaths in Directed Hypergraphs -- A Second-Order Cone Programming Approximation to Joint Chance-Constrained Linear Programs.-Extended Formulations, Nonnegative Factorizations, and Randomized Communication -- An Algebraic Approach to Symmetric Extended.-Gap Inequalities for the Max-Cut Problem: A Cutting-Plane Algorithm.
Keywords: Computer science; Computer Communication Networks; Computer software; Electronic data processing; Computational complexity; Algorithms; Computer Science; Algorithm Analysis and Problem Complexity; Discrete Mathematics in Computer Science; Numeric Computing; Algorithms; Computer Communication Networks